2018
DOI: 10.5588/ijtld.17.0371
|View full text |Cite
|
Sign up to set email alerts
|

Household context and psychosocial impact of childhood multidrug-resistant tuberculosis in KwaZulu-Natal, South Africa

Abstract: The socio-economic impact of childhood MDR-TB reverberates beyond diseased children to their affected households. Enhanced social protection, psychosocial support and treatment literacy would create the foundations for family-centred care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Previous studies reporting experiences of children and adolescents during DR-TB treatment included hospitalized patients, majority of whom were HIV co-infected [22,23]; while in our study, the participants were non-HIV and received DR-TB treatment on ambulatory basis. Though our study findings are in line with previous literature on paediatric DR-TB, our study contributes to the evidence around influence of families and communities in DR-TB treatment journey of children and adolescents.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies reporting experiences of children and adolescents during DR-TB treatment included hospitalized patients, majority of whom were HIV co-infected [22,23]; while in our study, the participants were non-HIV and received DR-TB treatment on ambulatory basis. Though our study findings are in line with previous literature on paediatric DR-TB, our study contributes to the evidence around influence of families and communities in DR-TB treatment journey of children and adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Group counselling sessions and support group meetings could be organized to discuss marriage concerns. To tackle stigma in community against DR-TB in general, mass awareness campaigns could be organized which will also aid in limiting TB transmission [23].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Definitions of 'acceptability' for anti-tuberculosis drugs or regimens may differ in different sociocultural contexts and should therefore be investigated more systematically in diverse settings. 29,30 Despite being given instructions on how to administer treatment, we observed that drug manipulation is common practice among caregivers who adapt and adopt different strategies to improve TB treatment administration to children. Further research is needed to confirm the pharmacokinetic implications of these real-life approaches to administration of anti-tuberculosis drugs (given with yoghurt or over a couple of hours).…”
Section: Discussionmentioning
confidence: 97%
“…However, as we did not capture household costs, we were unable to determine which model of care was most cost-effective to patients and society overall. Although the diagnosis and treatment of MDR-TB in South Africa is free, patients incur substantial costs accessing health services, with the poorest patients incurring the highest costs [ 32 , 33 ]. In some instances, when patients can continue with their household duties and return to work when they respond to treatment, community-based treatment will reduce household costs.…”
Section: Discussionmentioning
confidence: 99%